Loss analysis based on constant gate current for MOSFET selection of CCM boost converter. (8th December 2017) - Sasaki, Masato; Umegami, Hirokatsu; Yamamoto, Masayoshi
Abstract : Predicting the power losses in a semiconductor is an essential design process to determine the converter's size. In the continuous conduction mode (CCM) boost converter, the power loss of MOSFETs can be divided into the loss not depending on the gate current (the conduction loss) and losses depending on the gate current (the switching losses) leading to IDS transition period and VDS transition period. Therefore, analysis of both conduction and switching losses based on constant gate current can realize the MOSFET selection to improve the efficiency of the CCM boost converter.